Characterization of clinical extensively drug resistant Pseudomonas aeruginosa from a Chinese teaching hospital - Mingxiang Zou; Haichen Wang; Jian Shui; Jun Li; Yongmei Hu; Qingya Dou; Qun Yan; Wen' en Liu (Journal of Infection in Developing Countries)
Introduction: Pseudomonas aeruginosa, an important opportunistic pathogen, carries multiple virulence factors which contribute to its adaptation and pathogenicity. The goal of this study was to characterize the virulence factors among extensively drug-resistant P. aeruginosa.